Malaria and Early Life Immunity: Competence in Context - Callaway, Perri C.; Farrington, Lila A.; Feeney, Margaret E. (Frontiers in Immunology, 2021)
Childhood vaccines have been the cornerstone tool of public health over the past century. A major barrier to neonatal vaccination is the “immaturity” of the infant immune system and the inefficiency of conventional vaccine approaches at inducing immunity at birth. While much of the literature on fetal and neonatal immunity has focused on the early life propensity toward immune tolerance, recent studies indicate that the fetus is more immunologically capable than previously thought, and can, in some circumstances, mount adaptive B and T cell responses to perinatal pathogens in utero. Although significant hurdles remain before these findings can be translated into vaccines and other protective strategies, they should lend optimism to the prospect that neonatal and even fetal vaccination is achievable. Next steps toward this goal should include efforts to define the conditions for optimal stimulation of infant immune responses, including antigen timing, dose, and route of delivery, as well as antigen presentation pathways and co-stimulatory requirements. A better understanding of these factors will enable optimal deployment of vaccines against malaria and other pathogens to protect infants during their period of greatest vulnerability.